Models for Supply Chains in E-Business - Swaminathan, Jayashankar M.; Tayur, Sridhar R. (Management Science, 2003)
Supply chain management is likely to play an important role in the digital economy. In this paper, we first describe major issues in traditional supply chain management. Next, we focus our attention on the supply chain issues of visibility, supplier relationships, distribution and pricing, customization, and real-time decision technologies that have risen to importance with the prevalence of e-business. We present an overview of relevant analytical research models that have been developed in these areas, discuss their contributions, and conclude with a discussion on future modeling opportunities in this area.